Nursing of a patient with acute intestinal obstruction treated by moxibustion combined with Traditional Chinese Medicine enema (艾灸联合中药灌肠治疗1例急性肠梗阻患者的护理体会) - SU Guohua (苏国华); LIU Yunchao (刘云超); WANG Nannan (王楠楠); WANG Yue (王月); DONG Yuxia (董玉霞); TANG Ling (唐玲); E Haiyan (鄂海燕) (中西医结合护理)
This article summarized the moxibustion combined with Traditional Chinese Medicine (TCM) enema and related nursing measures for a patient with acute intestinal obstruction. The nursing goals were clarified based on the nursing assessment on illness condition and clinical symptoms of the patient. Guided by theory of syndrome differentiation, the moxibustion combined with TCM enema was carried out, in combination with routine care, to relieve the clinical symptoms of intestinal obstruction and pain of patient. (本文总结运用艾灸联合中药灌肠在治疗1例急性肠梗阻患者的护理经验。患者入院后及时完善护理评估, 明确护理目标, 通过辨证施护, 给予艾灸和中药灌肠干预, 同时配合常规的护理措施, 能有效改善肠梗阻患者不适症状, 减轻痛苦。)